Investigation and isolation of the active constituents of petroleum ether fraction of Medicago sativa L. sprouts - Seida, Ahmed A.; El-Hefnawy, Hala; Abou-Hussein, Dina R.; Mokhtar, Fatma Alzahraa (International Current Pharmaceutical Journal, 2013)
The unsaponifiable fraction from petroleum ether extract of Medicago sativa L. sprouts was analyzed by GLC, a series of 17 hydrocarbons and 2 phytosterols; ?-sitosterol and stigmasterol were identified. Analysis of the fatty acid fraction by GLC techniques revealed the presence of 6 saturated fatty acids and 8 unsaturated fatty acids including omega 6- fatty acid lionleic acid and 2 omega 3 fatty acids Eicosapentaenoic acid (EPA) and Docosahexaenoic acid (DHA) in a relative percent of 1.0% and 1.12%, respectively. These two types are rarely produced in plants but produced in fish, which have protective effects against heart diseases, liver functions and inflammations. DOI: http://dx.doi.org/10.3329/icpj.v2i6.14870 International Current Pharmaceutical Journal, May 2013, 2(6): 109-111